The active judge of the cuban procedural code in the debut of the constitutional effective judicial protection - Mendoza Díaz, Juan (2024)
The work develops the scenario that is generated in Cuba from 2019, when a new Constitution is approved, which abrogates the one in force since 1976. The new text regulates, for the first time, the effective judicial protection and due process within the chapter dedicated to the Guarantees of Rights and orders the ordinary legislator to dictate new rules of development in the different procedural areas, in charge of regulating the catalog of the new rights recognized in the Constitution. Derived from the constitutional mandate, Law No. 141, of October 28, 2021, “Procedural Code”, was enacted to regulate the processing of civil, family, commercial, labor and social security matters. The new Code, which breaks with the regulatory system of the preceding law, introduces a broad catalog of ordering and investigative powers, which are attributed to a model of judge described as “active”, whose powers are deployed throughout the new regulatory text and cover all procedural actions.